Ligand-enabled gold-catalyzed 1, 2-heteroarylation of alkenes. Issue 65 (15th July 2020) - Tathe, Akash G.; Chintawar, Chetan C.; Bhoyare, Vivek W.; Patil, Nitin T.
Abstract : By adopting the interplay between ligand-enabled Au(i )/Au(iii ) catalysis and the unique π-activation mode of gold complexes, a highly coveted 1, 2-heteroarylation of alkenes has been accomplished. Abstract : By adopting the interplay between ligand-enabled Au(i )/Au(iii ) catalysis and the unique π-activation mode of gold complexes, a highly coveted 1, 2-heteroarylation of alkenes has been accomplished. The present ligand-enabled approach not only circumvents the requirement for strong sacrificial oxidants or photocatalysts but also operates under mild reaction conditions by utilizing simple and non-prefunctionalized aryl coupling partners.